The bloody flag mutiny in the age of Atlantic revolution - Frykman, Niklas (California world history library, 2020)
Mutiny tore like wildfire through the wooden warships of the age of revolution. While commoners across Europe laid siege to the nobility and enslaved workers put the torch to plantation islands, out on the oceans, naval seamen by the tens of thousands turned their guns on the quarterdeck and overthrew the absolute rule of captains. By the early 1800s, anywhere between one-third and one-half of all naval seamen serving in the North Atlantic had participated in at least one mutiny, many of them in several, and some even on ships in different navies. In The Bloody Flag, historian Niklas Frykman